2018
DOI: 10.1177/0363546518775425
|View full text |Cite
|
Sign up to set email alerts
|

Primary Circumferential Acetabular Labral Reconstruction: Achieving Outcomes Similar to Primary Labral Repair Despite More Challenging Patient Characteristics

Abstract: Primary circumferential labral reconstruction is a viable treatment option with promising short-term outcomes for hips that demonstrate moderate or severe labral damage. Despite less favorable preoperative characteristics, labral reconstruction offers similar outcomes when compared with labral repair in hips with less severe pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
75
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 39 publications
3
75
0
Order By: Relevance
“…5,11 Recently, restoring the labral seal mechanism via labral reconstruction has emerged as a viable option as a result of new technology and innovative surgical techniques. 8,35,38 Arthroscopic labral reconstruction is not only complex but also a relatively new procedure. 15,16,29,37,41,44 Limited literature is available on short-and midterm outcomes after hip labral reconstruction.…”
mentioning
confidence: 99%
“…5,11 Recently, restoring the labral seal mechanism via labral reconstruction has emerged as a viable option as a result of new technology and innovative surgical techniques. 8,35,38 Arthroscopic labral reconstruction is not only complex but also a relatively new procedure. 15,16,29,37,41,44 Limited literature is available on short-and midterm outcomes after hip labral reconstruction.…”
mentioning
confidence: 99%
“…Ó 2020 Published by Elsevier on behalf of the Arthroscopy Association of North America 0749-8063/201134/$36.00 https://doi.org/10.1016/j.arthro.2020.06.036 support that approach, [22][23][24] whereas other studies have showed lower outcome scores for reconstruction but a statistical equivalence to repair. 25,26 Whether one believes in primary reconstruction or not, in my opinion, this study highlights the importance of the native labrum and the challenges we face with reconstructing it. From my perspective, intraoperative management of labral tissue from joint entry to preparation for pincer resection is extremely important and, if done poorly, can have long-term negative consequences for a patient.…”
Section: See Related Article On Page 2433mentioning
confidence: 81%
“…Other studies have shown similar promising results of labral reconstruction, particularly among patients with challenging hip problems, including those in whom prior treatment has failed, those who have higher preoperative pain scores, and those with more preoperative intra-articular pathology, as well as older patients. 17,25 This procedure may be particularly advantageous in patients aged 40 years and older, who may be more likely to have degenerative or poor-quality labral tissue and significant preoperative intra-articular pathology.…”
Section: Discussionmentioning
confidence: 99%